Profitability of different instruments in international climate policies - Finn Roar Aune; Snorre Kverndokk; Lars Lindholt; Knut Einar Rosendahl (Statistics Norway, Research Department, 2005)
This article discusses how different climate policy instruments such as CO2 taxes and renewable energy subsidies affect the profitability of fossil fuel production, given that a fixed global climate target shall be achieved in the long term. Within an intertemporal framework, the model analyses show that CO2 taxes reduce the short-term profitability to a greater extent than technology subsidies, since the competition from CO2-free energy sources does not become particularly noticeable until decades later. Due to e.g. discounting of future revenues, most fossil fuel producers therefore prefer subsidies to their competitors above CO2 taxes. However, this conclusion does not apply to all producers. Oil producers outside OPEC lose the most on the subsidising of CO2-free energy, while CO2 taxes only slightly reduce their profits. This is connected to OPEC's role in the oil market, as the cartel chooses to reduce its extraction significantly in the tax scenario. The results seem to be consistent with observed behaviour of important players in the climate negotiations.
Keywords: Q32; Q42; O30; Q25; 330; Climate policy; Energy markets; Technological change